2016
DOI: 10.1186/s12889-016-3320-6
|View full text |Cite
|
Sign up to set email alerts
|

Environmental predictors of stunting among children under-five in Somalia: cross-sectional studies from 2007 to 2010

Abstract: BackgroundStunting among children under five years old is associated with long-term effects on cognitive development, school achievement, economic productivity in adulthood and maternal reproductive outcomes. Accurate estimation of stunting and tools to forecast risk are key to planning interventions. We estimated the prevalence and distribution of stunting among children under five years in Somalia from 2007 to 2010 and explored the role of environmental covariates in its forecasting.MethodsData from househol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 31 publications
1
18
0
1
Order By: Relevance
“…Another key predictor of malnutrition was the lack of close monitoring of drought forecasts. The study showed that closer monitoring of climatic trends could provide valuable information for nutritional intervention planning [5]. In 2017, when our study was Never (n and %) 0 0 0 carried out, a nationwide famine was making assistance necessary to IDPs both in the camps and outside of them.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Another key predictor of malnutrition was the lack of close monitoring of drought forecasts. The study showed that closer monitoring of climatic trends could provide valuable information for nutritional intervention planning [5]. In 2017, when our study was Never (n and %) 0 0 0 carried out, a nationwide famine was making assistance necessary to IDPs both in the camps and outside of them.…”
Section: Discussionmentioning
confidence: 86%
“…Sustainable humanitarian assistance in terms of counselling or education in care practices may enhance caregivers' resilience in the long-term [31] when combined with other emergency efforts from time to time [4,5]. The distress caused by long term insecurity, lack of income and drought and the effect of recurrent emergencies on the emotional well-being and mental health of caregivers and children was not investigated in this study although it needs further attention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A mother’s behavior during her pregnancy and the caregiver’s behavior in early childhood can either mitigate or exacerbate the impact of modifiable environmental conditions on growth outcomes. Caregivers dictate or influence many exposures to a child in the first 1000 days of life [ 14 ], and while research has explored the biological and environmental factors that contribute to stunting [ 5 , 7 , 15 , 16 , 17 , 18 , 19 ], there is limited evidence on how caregiver behaviors may impact the outcome of stunting in their children in low income settings.…”
Section: Introductionmentioning
confidence: 99%
“…On top of the two mentioned famines, the rates of acute malnutrition have remained at very high levels since the start of the conflict, and they are among the highest in the world today. The causes of different forms of malnutrition in Somalia are multifactorial and linked to food insecurity and to morbidity and inadequate caring practices, all of them related to the disruption of peoples livelihood, destitution, large-scale population displacement and the limited access to basic services 2–4…”
Section: Introductionmentioning
confidence: 99%